2022
DOI: 10.3390/cancers14122843
|View full text |Cite
|
Sign up to set email alerts
|

CPX-351: An Old Scheme with a New Formulation in the Treatment of High-Risk AML

Abstract: Therapy-related acute myeloid leukemia (t-AML) and acute myeloid leukemia with myelodysplasia-related changes (AML-MRC) represent aggressive diseases characterized by a dismal prognosis if compared with de novo acute myeloid leukemia, especially in older patients. In these AML subsets, standard chemotherapy regimens produce poor response rates and unsatisfactory outcomes. Historically, conventional approaches consisted of an anthracycline combined with continuous infusion of cytarabine for 7 days, the “3+7” re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…41,44,45 In an effort to improve patient survival, liposomal delivery of anticancer agents improves targeted drug delivery to cancer cells and thus enhances drug efficacy. 22,25 In this study, biodistribution data demonstrated a significant increase of MP-A08 accumulation in the bone marrow of mice treated with MP-A08-liposomes compared with MP-A08 as a free compound, despite approximately 100 times lower dosing of MP-A08 employed for MP-A08-liposomes. It is worth noting that liposomes rely on passive targeting to leukemic cells in the bone marrow, and we have strategically engineered our liposomes with DMPC and DPPG lipids, comprising a mixture of zwitterionic and negatively charged phospholipids, that enhance MP-A08 uptake by phospholipid binding with the high level of scavenger receptor class Bl expression on leukemic cells.…”
Section: ■ Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…41,44,45 In an effort to improve patient survival, liposomal delivery of anticancer agents improves targeted drug delivery to cancer cells and thus enhances drug efficacy. 22,25 In this study, biodistribution data demonstrated a significant increase of MP-A08 accumulation in the bone marrow of mice treated with MP-A08-liposomes compared with MP-A08 as a free compound, despite approximately 100 times lower dosing of MP-A08 employed for MP-A08-liposomes. It is worth noting that liposomes rely on passive targeting to leukemic cells in the bone marrow, and we have strategically engineered our liposomes with DMPC and DPPG lipids, comprising a mixture of zwitterionic and negatively charged phospholipids, that enhance MP-A08 uptake by phospholipid binding with the high level of scavenger receptor class Bl expression on leukemic cells.…”
Section: ■ Discussionmentioning
confidence: 59%
“…In addition, MP-A08-liposomes demonstrate enhanced bone marrow biodistribution (Figure A), which could be another factor contributing to the survival of mice engrafted with AML. One of the root causes of AML poor prognosis is the presence of leukemic stem and progenitor cells (LSPC) in the bone marrow microenvironment. These cells are resistant to conventional chemotherapy regimens, persist within the bone marrow microenvironment during patient therapy, and drive disease relapse. ,, In an effort to improve patient survival, liposomal delivery of anticancer agents improves targeted drug delivery to cancer cells and thus enhances drug efficacy. , In this study, biodistribution data demonstrated a significant increase of MP-A08 accumulation in the bone marrow of mice treated with MP-A08-liposomes compared with MP-A08 as a free compound, despite approximately 100 times lower dosing of MP-A08 employed for MP-A08-liposomes. It is worth noting that liposomes rely on passive targeting to leukemic cells in the bone marrow, and we have strategically engineered our liposomes with DMPC and DPPG lipids, comprising a mixture of zwitterionic and negatively charged phospholipids, that enhance MP-A08 uptake by phospholipid binding with the high level of scavenger receptor class Bl expression on leukemic cells .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of liposomal-based drug delivery has the potential to significantly improve patient outcomes. Recent evidence of novel liposomal CPX-351 (also known as Vyxeos ® ), a cytarabine and daunorubicin liposomal formulation approved by the FDA to treat newly diagnosed therapy-related AML or AML with myelodysplasia-related changes [ 23 , 37 , 38 , 39 , 40 , 41 , 42 ], has emphasized the importance of nanomedicine in the treatment of AML. Indeed, recent work in our laboratory employing a reliable platform of liposomal encapsulation to effectively deliver MP-A08 to eradicate human AML cells engrafted in mice and significantly enhance mice survival was a remarkable breakthrough [ 17 ], demonstrating the potential of the MP-A08 liposomal formulation as a promising monotherapy against AML.…”
Section: Discussionmentioning
confidence: 99%